The Usage of the Flipped Class Model when Teaching International Students Theoretical Disciplines at the Philological Faculty (Proceedings of the International Conference on Future of Education, 2021)
One of the teaching models which stimulates and motivates students' studying activities isthe flipped class, which “turns over” the traditional order of the material (a lecture - homework) viceversa. The purpose of this work is to present the effectiveness of the usage of the flipped class modelwhen teaching international students’ theoretical disciplines in Russian at the philological faculty atPushkin State Russian Language Institute. The traditional way of giving the material of theoreticaldisciplines to the international students didn’t show the high results: the students couldn’t master thematerial in full, didn’t understand texts of the lectures due to an insufficiently formed lexical stockand couldn’t do practical tasks and tests. The students met significant difficulties during theperformance of the certification work. It became clear that the special preparative work must be donewith the students before they begin to listen to lectures. So, the teaching and academic staff of thedepartment (Department of Methodology of Teaching Russian as a Foreign Language) at thephilological faculty decided to change the traditional way of giving theoretical lecture material inRussian for the international students into the flipped class teaching model. In 2019-2020 academicyear the international students got the new formatted material under study within the theoreticaldiscipline “Aspect study of the Russian Language in an international audience”. LMS Canvas wasused as an educational platform, where the students got different tasks with video lectures, articles,questions, practical exercises. At the end of the term the students completed the certification work.And the high points which the students got for the work indicated the correctness of the chosenteaching model.
Keywords: teaching international students; traditional format of teaching; flipped class teaching model; Russian and international audience